2021
DOI: 10.1253/circj.cj-21-0133
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Study of Placentas From Women With a Fontan Circulation

Abstract: Background: Pregnant women with a Fontan circulation have a high risk of obstetric complications, such as preterm delivery and small for gestational age (SGA), which may be affected by low blood flow to the placenta and hypoxia. This study investigated placental pathology in a Fontan circulation. Methods and Results:Eighteen pregnancies in 11 women with a Fontan circulation were reviewed. Pregnancy outcomes showed 9 miscarriages and 9 live births, with 4 preterm deliveries. Five neonates were SGA (<5th percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Philips et al found prominent sub-chorionic fibrin deposition in all placentas ( 110 ). In the study by Yokouch-Konishi et al ( 109 ) seven of eight placentas had a chronic subchorionic hematoma. Other histopathologic changes included lesions associated with maternal vascular malperfusion, villous stromal fibrosis, and placental hypervascularity.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…Philips et al found prominent sub-chorionic fibrin deposition in all placentas ( 110 ). In the study by Yokouch-Konishi et al ( 109 ) seven of eight placentas had a chronic subchorionic hematoma. Other histopathologic changes included lesions associated with maternal vascular malperfusion, villous stromal fibrosis, and placental hypervascularity.…”
Section: Resultsmentioning
confidence: 93%
“…Our search returned 4 articles in total, of which 3 articles regarding abnormalities in the female sex organs ( 109 111 ) and one regarding sexual function in males ( 112 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations